Harriot Stanton Blatch papers - Blatch, Harriot Stanton, 1856-1940.
Scrapbooks containing correspondence, questionnaires, annual reports of the Women's Political Union, other reports, pamphlets, clippings, photographs, memorabilia, and additional material documenting the struggle for women's suffrage in New York State, culminating with the passage of the suffrage amendment in the state legislature in 1915. Also includes material marking the centennial celebration of the birth of Blatch's mother, Elizabeth Cady Stanton.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Photostats produced from originals in the Manuscript Division.
Suffragist and founder of the Equality League of Self-Supporting Women, later the Women's Political Union.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Stanton, Elizabeth Cady, -- 1815-1902 -- Anniversaries, etc; New York (State). -- Legislature; Women's Political Union (New York, N.Y.); Women -- Suffrage -- New York (State); Suffragists